Failure of Single‐Dose Methotrexate in a Cornual Pregnancy and Successful Laparoscopic Wedge Resection: A Case Report - Azadeh Tarafdari; Hawraa Shbeeb; Huma Homam (Clinical Case Reports)
ABSTRACT Early sonographic diagnosis of cornual pregnancy is vital, yet medical therapy with single‐dose methotrexate carries a considerable failure rate. Prompt transition to laparoscopic resection when beta‐HCG (human chorionic gonadotropin hormone) plateaus or clinical status deteriorates averts catastrophic rupture while preserving fertility.